2014
DOI: 10.1107/s205322961402258x
|View full text |Cite
|
Sign up to set email alerts
|

Hobartine: a tetracyclic indole alkaloid extracted fromAristotelia chilensis(maqui)

Abstract: The natural compound hobartine {systematic name: (1R)-3-[(1S,5S)-(4,4,8-trimethylbicyclo[3.3.1]non-7-en-2-yl)methyl]-2,3-dihydro-1H-indole}, C20H26N2, (I), is an indole alkaloid isolated from Aristotelia chilensis as part of a study of secondary metabolites from Chilean flora. The colourless compound has a tetracyclic structure closely related to the strongly coloured polymorphic structures discussed in Paz et al. [Acta Cryst. (2013), C69, 1509-1512] and Watson et al. [Acta Cryst. (1989), C45, 1322-1324]. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Only a few studies refer to the phytochemical analysis of leaf extracts of Maqui. The presence of indole and quinoline alkaloids has been reported in the leaves [ 19 ], being identified as aristoteline, serratoline, aristone, horbatinol, and horbatina [ 54 , 55 ]. Studies performed on ethanolic extracts of Maqui leaves reported the presence of some polyphenols such as gallic acid, coumaric acid, quercetin, myricetin, rutin, pelargonidin, and catechin.…”
Section: Chemical Characterization Of Maquimentioning
confidence: 99%
“…Only a few studies refer to the phytochemical analysis of leaf extracts of Maqui. The presence of indole and quinoline alkaloids has been reported in the leaves [ 19 ], being identified as aristoteline, serratoline, aristone, horbatinol, and horbatina [ 54 , 55 ]. Studies performed on ethanolic extracts of Maqui leaves reported the presence of some polyphenols such as gallic acid, coumaric acid, quercetin, myricetin, rutin, pelargonidin, and catechin.…”
Section: Chemical Characterization Of Maquimentioning
confidence: 99%